The Satyam Scandal and Creative Accounting: An Analysis of Impact, Causal Factors, and Lessons for Corporate Governance in Indonesia - Ardiansyah, Ardiansyah (Institut Bisnis dan Informatika Kesatuan, 2026)
The Satyam Computer Services Limited accounting scandal is one of the largest financial frauds in India, exposing extensive creative accounting practices that undermined financial reporting integrity. The case involved the manipulation of financial statements through fictitious revenues and false cash balances, reflecting weaknesses in internal controls, ineffective board oversight, and inadequate external audit performance. This study aims to analyze the Satyam scandal using the fraud triangle framework and to identify its implications for corporate governance and audit quality, particularly for developing capital markets such as Indonesia. This research employs a descriptive qualitative method using library research. Data were collected from academic literature, audit reports, regulatory documents, and credible media sources, and analyzed using content analysis based on the fraud triangle theory. The findings indicate that the fraud was driven by strong financial pressure to maintain company performance, opportunities arising from weak governance and control systems, and rationalization by management to justify unethical actions. The Satyam scandal demonstrates that corporate fraud is not only an accounting failure but also a governance and ethical failure. The study highlights the importance of strengthening corporate governance, improving audit quality, and enhancing transparency to prevent similar cases in emerging markets such as Indonesia.